GERMINATION OF PRE-SOAKED SEEDS AND INITIAL GROWTH OF Artocarpus heterophyllus Lam. PLANTS - LIMA, Juliana Firmino de; FONSECA, Valdir José de Almeida; MORAES, José Carlos de Cerqueira; de ALMEIDA, Jorge; VIEIRA, Elvis Lima; PEIXOTO, Clovis Pereira (Scientia Agraria, 2009)
The Experiment was installed in the greenhouse at the Center of Agricultural, Environmental and Biological Sciences at the Federal University of the Reconcavo Region of Bahia, aiming to evaluate the germination of pre-soaked seeds and initial growth of Artocarpus heterophyllus Lam. plants. The complete random block design was used with fine treatments and four replicates. The treatments were as follows: T1- distilled water, T2- liquid gibberelin at 200 cm3 dm-3, T3 - Stimulate® at 5 cm3 dm-3 and T4 - Stimulate® at 10 cm3 dm-3. Sowing was carried out in plastic trays with the concave side of the seeds facing downward and covered with a layer of sand. The substrate was humidified with water until reaching 60% of the hydric saturation, which were remained in counters under (25+2 ºC) room temperature. The variables evaluated were: number of days until the beginning of seed germination, number of days to finalize germination, germination percentage, root length, stem length, number of leaves, root dry matter, stem dry matter, leaf dry matter, total plant dry matter 35 days after sowing and germination rate. Data was submitted to the analysis of variance, averages compared by the Tukey test at 5% probability. The pre-soaking of the seeds of hard jack fruit in distilled water, and Stimulate® can be indicated for the production of seedlings with higher height.